(untitled) (The Review of Diabetic Studies, 2025)
Diabetic foot disease represents a major cause of morbidity, limb loss, and healthcare burden among individuals with diabetes, particularly when compounded by peripheral arterial disease and chronic limb-threatening ischemia. Interventional radiology has become a cornerstone in limb salvage through minimally invasive, imaging-guided endovascular therapies. However, optimal clinical outcomes depend not only on technical success but also on coordinated nursing care and effective use of health informatics to enhance patient safety. This integrative review examines the role of interventional radiology in diabetic foot disease through a multidisciplinary framework that incorporates imaging-guided therapies, structured nursing pathways, and health informatics–supported care. A structured literature review of peer-reviewed studies published between 2010 and 2024 was conducted across major biomedical databases, focusing on endovascular interventions, nursing roles across procedural phases, and informatics applications relevant to safety and continuity of care, in alignment with international vascular and diabetic foot management guidelines (Hingorani et al., 2016; Conte et al., 2019). The findings indicate that imaging-guided endovascular interventions, including percutaneous transluminal angioplasty and adjunctive technologies, are associated with improved limb salvage and wound healing when appropriately planned using advanced imaging modalities. Structured nursing pathways significantly contribute to risk mitigation through pre-procedural assessment, intra-procedural monitoring, and post-procedural surveillance and education. Health informatics systems, including electronic health records and imaging informatics, facilitate interdisciplinary communication, clinical decision support, and longitudinal outcome tracking, thereby reducing preventable complications. Synthesized clinical case studies further demonstrate how integration of these domains enhances safety and patient-centered outcomes. In conclusion, interventional radiology achieves its greatest impact in diabetic foot disease when embedded within standardized nursing pathways and supported by robust health informatics infrastructure. This integrated, safety-oriented model offers a scalable approach to improving limb preservation and quality of care in high-risk diabetic populations.